ANALYSIS OF MEASURED EXPENDITURES AND INCOME OF RUSSIAN HOUSEHOLDS - Maxym V. Bryukhanov; Sergiy S. Polyachenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
In this study, using data drawn from RLMS (1994-2014) we present generalized analysis of structural dynamics of income and expenditure parts of urban and rural household budgets in Russia in the context of consumption smoothing theory. Employing index of structural dynamics known as Ryabtsev index we defined periods of the most significant structural changes in income and expenditures of Russian population. Our calculations show that the most of changes in income and expenditures took place during the crisis of 1998 and the boost of 2006. Analysis of changes suggests that consumption preferences of Russian people lie in the framework of consumption smoothing theory.